2001
DOI: 10.1046/j.1523-536x.2001.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Position for Newborn Sleep: Associations with Parents' Perceptions of Their Nursery Experience

Abstract: Perceptions by parents of instructions from a doctor or a nurse of the position in which the infants were placed in the nursery were associated with the position parents reported placing their infants to sleep at home. Efforts to promote the supine sleeping position in the inner-city setting should address both practices and education provided to parents in the nursery during the postpartum hospital stay and should be sufficiently powerful to align their perceptions of the postpartum experience with current Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 12 publications
1
38
0
3
Order By: Relevance
“…and role modeling to families and providers. Studies have demonstrated that supine position and bed sharing at home are both positively and negatively influenced by SSP modeled in the newborn nursery 4,5 and sleep advice provided by health care professionals. 6 -8 Given this influence of SSP modeling from the newborn nursery, we were concerned about potentially negative influence of unsafe sleep practices modeled in inpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…and role modeling to families and providers. Studies have demonstrated that supine position and bed sharing at home are both positively and negatively influenced by SSP modeled in the newborn nursery 4,5 and sleep advice provided by health care professionals. 6 -8 Given this influence of SSP modeling from the newborn nursery, we were concerned about potentially negative influence of unsafe sleep practices modeled in inpatient settings.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that parent practices at home are strongly influenced by hospital nursery practices when it comes to the topic of SIDS. 27,36,37 Therefore, altering an infant's sleep regimen by removing one component from it, pulse oximetry monitoring, may be unsettling to parents and cause unnecessary anxiety. Since medical protocols should be based in evidence, and there is no evidence behind this protocol, there should be no need to monitor these otherwise healthy infants.…”
Section: Discussionmentioning
confidence: 99%
“…None of the citations included any evidence specifically addressing whether electronic monitoring of infants in the prone position for sleep reduced incidence of SIDS. 1,4,5,[23][24][25][26][27][28][29] The goal was then to determine if there is evidence in the literature specifically addressing the question: does pulse oximetry monitoring of otherwise healthy infants (i.e. those not at increased risk for SIDS) put to sleep in the prone position reduce the incidence of SIDS?…”
Section: Methodsmentioning
confidence: 99%
“…Caregivers are more likely to engage in safe infant sleep if these practices are modeled by providers in the hospital. 11 In addition, multiple sources of consistent messaging are more likely to increase the likelihood that mothers will practice safe sleep with their infants, 12 and the hospital provides 1 of many opportunities for families to engage in and establish safe sleep practices with their newborns.…”
mentioning
confidence: 99%